Political Marketing and Social Media - Gierlach, Karina (Historia i Polityka, 2026)
This paper explores the evolving subject of political marketing, which integrates principles of commercial marketing into the political sphere to strategically influence voter behavior, shape public discourse and guide institutional processes. While political marketing draws heavily on concepts such as market orientation and customer satisfaction, it diverges from commercial marketing by addressing the unique complexities of democratic systems. The rise of digital technologies – particularly the Internet and social media – has transformed political marketing, enabling direct, personalized and data-driven communication between politicians and citizens. These platforms have expanded political engagement, amplified campaign messaging and facilitated the spread of cultural tools like memes. However, they also introduce challenges related to misinformation, reputational risk and the sustainability of democratic processes. The study examines theoretical foundations, key definitions, and real-world applications of political marketing, with a focus on how digital media have reshaped campaign strategies and citizen interaction. Ultimately, the paper highlights the dual role of political marketing as both a tool for engagement and a force that must be managed responsibly within democratic societies.